I felt so much conflict instead of joy: an analysis of open-ended comments from people in British Columbia who declined care recommendations during pregnancy and childbirth - Kathrin Stoll; Jessie J. Wang; Paulomi Niles; Lindsay Wells; Saraswathi Vedam (BMC, 2021)
Abstract Background No Canadian studies to date have examined the experiences of people who decline aspects of care during pregnancy and birth. The current analysis bridges this gap by describing comments from 1123 people in British Columbia (BC) who declined a test or procedure that their care provider recommended. Methods In the Changing Childbirth in BC study, childbearing people designed a mixed-methods study, including a cross-sectional survey on experiences of provider-patient interactions over the course of maternity care. We conducted a descriptive quantitative content analysis of 1540 open ended comments about declining care recommendations. Results More than half of all study participants (n = 2100) declined care at some point during pregnancy, birth, or the postpartum period (53.5%), making this a common phenomenon. Participants most commonly declined genetic or gestational diabetes testing, ultrasounds, induction of labour, pharmaceutical pain management during labour, and eye prophylaxis for the newborn. Some people reported that care providers accepted or supported their decision, and others described pressure and coercion from providers. These negative interactions resulted in childbearing people feeling invisible, disempowered and in some cases traumatized. Loss of trust in healthcare providers were also described by childbearing people whose preferences were not respected whereas those who felt informed about their options and supported to make decisions about their care reported positive birth experiences. Conclusions Declining care is common during pregnancy and birth and care provider reactions and behaviours greatly influence how childbearing people experience these events. Our findings confirm that clinicians need further training in person-centred decision-making, including respectful communication even when choices fall outside of standard care.